The effect of race/ethnicity on active treatment rates among septuagenarian or older low risk prostate cancer patients - Nocera, Luigi; Wenzel, Mike; Collà Ruvolo, Claudia; Würnschimmel, Christoph; Tian, Zhe; Gandaglia, Giorgio; Fossati, Nicola; Chun, Felix K H; Mirone, Vincenzo; Graefen, Markus; Shariat, Shahrokh F; Saad, Fred; et al. (Urologic oncology, 2021)
BACKGROUND: Race/ethnicity may predispose to higher active treatment rates in septuagenarian or older low risk prostate cancer (CaP) patients. We tested this hypothesis within a contemporary North American cohort. MATERIAL AND METHODS: We relied on the Surveillance, Epidemiology and End Results (SEER) database 2010-2016. The effect of race/ethnicity was tested in univariable and multivariable logistic regression analyses predicting definitive treatment administration. Treatment rates (no local treatment [NLT], external beam radiotherapy [EBRT], radical prostatectomy [RP] and brachytherapy) were examined without, as well as with adjustment for age, socioeconomic status, marital status, residence type, year of diagnosis, other-cause mortality, prostate-specific antigen (PSA) and clinical T stage across races/ethnicities. Moreover, temporal trend analyses were performed. RESULTS: Of 15,118 septuagenarian or older low risk CaP patients, 11,509 (76.1%) were Caucasian, 1,613 (10.7%) African-American, 1,293 (8.5%) Hispanic/Latino and 703 (4.7%) Asian. No clinically meaningful differences were recorded between races/ethnicities with respect to age at diagnosis, PSA, clinical T stage and percentage of positive biopsy cores. Conversely, clinically meaningful and statistically significant differences were identified in socioeconomic status and treatment modality. Specifically, treatment rates ranged as follows: NLT 41.8-48.2, EBRT 23.0-29.9, RP 13.8-21.8 and brachytherapy 6.4-9.9% across race/ethnicies. After adjustment for patient and tumor characteristics, NLT, EBRT, RP and brachytherapy rates showed virtually no residual heterogeneity between races/ethnicities. Finally, in temporal trend analyses, EBRT rates decreased in all races/ethnicities. Conversely, RP and brachytherapy rates did not change over time. CONCLUSION: The rates of active treatment in septuagenarian or older low risk CaP patients are surprisingly elevated in all races/ethnicities, even though they decreased over time. All differences in active treatment rates according to race/ethnicity depend on baseline patient and tumor characteristics.
Keywords: Aged, 80 and over; Prostatic Neoplasms; African-American; etnicita; nádory prostaty; senioři nad 80 let; Aged; CaP; Asian; Humans; Ethnicity; SEER; mužské pohlaví; senioři; lidé; Male; Hispanic/Latino